FAKTOR-FAKTOR YANG MEMPENGARUHI PENURUNAN PRODUKSI MINYAK KELAPA MURNI (LENGIS TANUSAN) DI DESA ANTIGA, KARANGASEM - I Nyoman Sunada (JURNAL GASTRONOMI INDONESIA, 2021)
The purpose of this study is to identify and describe the factors that influence the decline in the production of virgin coconut oil (lengis tanusan) in Angtiga Village, Karangasem, and the benefits of this research are expected to be information to the world of the catering industry and the public that virgin coconut oil has many benefits. advantages of ordinary vegetable oil. The theory used to solve the problem in this research is "Production Management" which discusses the factors of production, such as: Humans (Labour), Methods, Machines, Raw Materials and Types of Production. The research method, the object of this research is Pure Coconut Oil (lengis tanusan) in Antiga Village, Karangasem which is obtained from the results of observations and interviews. The data analysis technique in this research is descriptive qualitative. Based on the results of research that has been carried out at a virgin coconut oil production house in Antiga Village, Karangasem and discussions related to the factors that affect the decrease in the amount of production, it can be concluded that: Workers who are not given training so they are less able to work more effectively and efficiently, the method used in the manufacture of virgin coconut oil using heating, the lack of use of appropriate machines and the use of raw materials (coconut) is not maintained.